The effect of chronic kidney disease on the urine proteome in the domestic cat (Felis catus). Issue 1 (April 2015) - Ferlizza, E.; Campos, A.; Neagu, A.; Cuoghi, A.; Bellei, E.; Monari, E.; Dondi, F.; Almeida, A.M.; Isani, G.
Highlights Chronic kidney disease is a major cause of mortality in cats, but sensitive and specific biomarkers are currently lacking. This study aimed to apply proteomic techniques to map the cat urine proteome and compare it with that in cats with CKD. Our work produced a reference map of the normal cat urine proteome containing 20 proteins identified by mass spectrometry. We identified 13 proteins differentially represented in CKD. Most of these proteins are indicative of tubulointerstitial damage when not reabsorbed or not secreted.